Peak Performance Related to the Athletes' Mental Toughness at the Speed Athletics Club Yogyakarta, Indonesia - Titik Muti'ah; Arifin; Jewelson M. Santos (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2024)
This study aims to determine the relationship between mental toughness and peak performance. The hypothesis proposed in this study is whether positive relationship between mental toughness and peak performance among the athletes who join the Speed ​​Athletic Club Yogyakarta. The population were 52 athletes, with sampling technique was a saturated sample, (where all members of the population became the research sample). Data were analyzed by product moment correlation from Pearson with SPSS 23 for Windows program. The results showed r = 0.836 with a value of p = 0.000 (p <0.05), meaning that the hypothesis is accepted. This study found a positive and significant relationship between mental toughness and peak performance in athletes in the speed athletic club. The effective contribution of mental toughness to peak performance is 69.9% and the remaining 30.1% is influenced by other factors not measured in this study.